2023
DOI: 10.1021/acschembio.2c00783
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Unexpected Self-Acylation Activity of Acyl Carrier Proteins in a Modular Type I Apicomplexan Polyketide Synthase

Abstract: Natural products play critical roles as antibiotics, anticancer therapeutics, and biofuels. Polyketides are a distinct natural product class of structurally diverse secondary metabolites that are synthesized by polyketide synthases (PKSs). The biosynthetic gene clusters that encode PKSs have been found across nearly all realms of life, but those from eukaryotic organisms are relatively understudied. A type I PKS from the eukaryotic apicomplexan parasite Toxoplasma gondii,TgPKS2, was recently discovered through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…These self-acylating ACPs are capable of loading a large scope of CoA substrates onto their ppant arms without an AT domain, which is conventionally required for this activity. 49 The TgPKS2 putative release didomain is also unusual as it contains a KS and TR domain. Predominantly, a thioester reductase or thioesterase is preceded by an ACP domain.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These self-acylating ACPs are capable of loading a large scope of CoA substrates onto their ppant arms without an AT domain, which is conventionally required for this activity. 49 The TgPKS2 putative release didomain is also unusual as it contains a KS and TR domain. Predominantly, a thioester reductase or thioesterase is preceded by an ACP domain.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The protein contains three defined modules and hypothetical loading and release didomains. Biochemical characterization of the AT and ACP domains revealed unexpected activities. , For instance, a unique self-acylation activity is observed with three of the four Tg PKS2 ACP domains ( Tg ACP2–4). These self-acylating ACPs are capable of loading a large scope of CoA substrates onto their ppant arms without an AT domain, which is conventionally required for this activity .…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of Tg PKS2 revealed an 18.8 kb gene that encodes a single ∼680 kDa modular type I PKS (Figure 4A). [102] antiSMASH analysis of this protein indicates three distinct modules with multiple interesting features, including a hypothesized loading module devoid of a definitive AT domain. This domain arrangement (KS‐ACP) has been previously observed and characterized in a recently de‐orphanized Nocardia PKS where it was found that the loading KS domain had decarboxylative activity and modified malonyl‐ S ‐ACP to acetyl‐ S ‐ACP [103] .…”
Section: Domain Architecture and Characterization Of Apicomplexan Pkssmentioning
confidence: 99%